γ-PNA PREORGANIZATION: SYNTHESIS OF MODEL DIMER AND ITS STRUCTURE STUDY BY 2D NMR SPECTROSCOPY - A. V. Dezhenkov; D. A. Cheshkov; I. A. Prokhorov; A. I. Lutik; Yu. G. Kirillova (Тонкие химические технологии, 2017)
The synthesis of a dimer consisting of γ-thymine chiral monomer based on L-Ala and thymine aeg-PNA monomer (synthesized from deuterated glycine), in which the methylene protons of the pseudopeptide residue were exchanged with deuterium atoms, was described. The deuterated monomer was introduced into acylation reaction by means of a mixed anhydride procedure with γ-PNA chiral monomer trifluoroacetate based on L-Ala. The latter was obtained from the fully protected thymine monomer by the reaction with trifluoroacetic acid. The structure and purity of the target monomer were confirmed by NMR-spectroscopy, and the elemental composition was estimated by quantitative elemental analysis. The double quantum filtered COSY-NMR-spectroscopy (DQF-COSY) method was used to determine the methylene signals of the dimer chiral fragment. With the use of the spectrum analysis, the chemical shifts and calculated spin-spin coupling constants of the protons from the dimer chiral part were found. Given that Karplus equation associates the value of the dihedral angle between the vicinal protons with their spin-spin coupling constant, it was concluded that the chiral fragment is in the right-helix conformation for all the dimer rotamers.